Feeding Habits of The Thin Lip Grey Mullet Liza Ramada (Risso, 1810) (Pisces, Mugilidae) From Sousa Coast, Eastern Libya - Eman Rasheed; Hana Saleh; Hanen Hamed (AlQalam Journal of Medical and Applied Sciences, 2021)
The feeding habits of Liza ramada (family: Mugilidae) inhabiting Sousa Mediterranean coast were studied using a total of 203 specimens collected monthly during April 2017 to March 2018. Stomach contents of each fish was studied by points of assessment to establish food and feeding habits of the fish, including annual diet composition, variation of diet composition and feeding intensity, during different months and seasons. Length of studied Liza ramada ranged from 19.4 to 50.8 cm. Liza ramada fed on a wide variety of prey types: sediment, algae (36%), polychaetes (35%), diatoms (16.2%), crustaceans “mainly small prawns, crabs, copepods, and amphipod” (6.2 %), sediment (3.4 %), foraminifera (2.3%) and fish parts (1%). In April, May and June, Liza ramada consumed Algae by values of 44%, 37% and 35.5% respectively, diatoms by 46% in April, sediment by 59.28% in October, polychaetes by 40% in December, crustaceans by 62.74% in January, foraminifera by 1.2% in November, and fish parts by 6.7 % and 18 % in February and March respectively. Algae were completely absent from the diet during January. Algae diatoms, Polychaetes and foraminifera were consumed by all length groups of Liza ramada. Contribution of sediment and polychaetes decreased as fish length increased, while that of Algae increased. The feeding activity of the Liza ramada was high during spring (58.33 %) and winter (35.59 %) and low during summer (14.96 %) and autumn (23.9 %).